New insights from reactivity testing of supplementary cementitious materials. (October 2019) - Suraneni, Prannoy; Hajibabaee, Amir; Ramanathan, Sivakumar; Wang, Ying; Weiss, Jason
Abstract: Tests to determine the reactivity of supplementary cementitious materials (SCMs) by using isothermal calorimetry and thermogravimetric analysis have been proposed. In one such test, the heat release and calcium hydroxide consumption of SCMs mixed with calcium hydroxide (3:1 ratio of calcium hydroxide and SCM) at 50 °C in a 0.5 M potassium hydroxide environment are measured. In this study, we show the results of such testing for a large variety of SCMs and fillers, ranging from conventional materials such as fly ash, slag, silica fume, quartz, and limestone, to alternative materials such as calcined clays, municipal solid waste incineration fly ash, basic oxygen furnace slag, ground lightweight aggregates, ground pumice, ground glass pozzolan, and basalt fines. A total of 54 SCMs are tested using this approach. Results show that even among SCMs of the same type, there is considerable difference in the heat release and calcium hydroxide consumption, likely due to differences in amorphous content, chemical composition, and fineness, leading to different reactivities. Based on the response in the test, SCMs are classified into inert, pozzolanic, and latent hydraulic; the pozzolanic and latent hydraulic materials are further classified into less reactive and more reactive. The relationship between heat release and calcium hydroxide consumption depends on the chemical composition of the SCMs, and SCMs with high calcium, high alumina, and high silica contents show different relationships (determined by the slope of the heat release vs. calcium hydroxide plot).